Comparative study of tetrasulfonated phthalocyanine modified screen-printed electrodes in paraquat - Kavazoi, Henry S. [UNESP]; Martin, Cibely S. [UNESP]; Alessio, Priscila [UNESP] (Elsevier, 2022)
Emerging pollutants, including pesticides, have been an increasing problem to human and environmental health. Based on this, the development and optimization of sensors is an essential approach to controlling emerging pollutants. Here, screen-printed carbon electrodes (SPCE) modified with three MTsPc (FeTsPc, CuTsPc, or NiTsPc) were evaluated for voltammetric detection of paraquat (PQ). UV-Vis absorption and Raman spectroscopy coupled with optical microscopy were used to prove the metal center directly influences the aggregation of MTsPc on the electrode surfaces, which promotes variation on the redox couple of PQ. The adsorption of PQ2+ species was proportional to aggregation of MTsPc following the order FeTsPc > NiTsPc > CuTsPc. The FeTsPc/SPCE showed a better voltammetry response for PQ detection in both ultrapure and river water, being applied in sensing measurements. The differential pulse voltammetry analysis showed a linear range of 6.0–60 µmol/L with a limit of detection of 0.97 µmol/L in the standard sample and recovery of 103.3% in the river sample. The results indicate an excellent pertinence of sensing applications and the possibility of developing cheap devices.
Keywords: Electrochemical sensor; Pesticide; River water; Surface modification